Glycaemic index and optimal performance - Walton, P.; Rhodes, E. C. (Sports Medicine, 1997)
It is widely documented that athletes should consume carbohydrates prior to, during and after exercise. Ingestion of carbohydrates at these times will optimise performance and recovery. In spite of this knowledge, there is a paucity of information available to athletes concerning the types of carbohydrate foods to select. Therefore, it is suggested that the glycaemic index may be an important resource when selecting an ideal carbohydrate. The glycaemic index categories foods containing carbohydrates according to the blood glucose response that they elicit. Carbohydrate foods evoking the greatest responses are considered to be high glycaemic index foods, while those producing a relatively smaller response are categorised as low glycaemic index foods. Athletes wishing to consume carbohydrates 30 to 60 minutes before exercise should be encouraged to ingest low glycaemic index foods. Consuming these types of foods will decrease the likelihood of creating hyperglycaemia and hyperinsulinaemia at the onset of exercise, while providing exogenous carbohydrate throughout exercise. It is recommended that high glycaemic index foods be consumed during exercise. These foods will ensure rapid digestion and absorption, which will lead to elevated blood glucose levels during exercise. Post-exercise meals should consist of high glycaemic index carbohydrates. Low glycaemic foods do not induce adequate muscle glycogen resynthesis compared with high glycaemic index foods.